Ghrelin, leptin and adiponectin levels in Gaucher disease type I patients on enzyme replacement therapy - Doneda, Divair; Lopes, André L.; Teixeira, Bruno C.; Mittelstadt, Suzana D.; Moulin, Cileide C.; Schwartz, Ida V.D. (Clinical nutrition (Edinburgh, Scotland), 2015)
Gaucher disease type I (GD type I) is characterized by clinical heterogeneity and is associated with metabolic abnormalities such as increased basal metabolic rate. To evaluate ghrelin, leptin and adiponectin levels in patients with GD type I on enzyme replacement therapy (ERT). A cross-sectional study of patients with GD type I (n = 15), matched for sex, age and BMI with healthy controls. The levels of glucose, insulin, ghrelin, leptin and adiponectin were assessed in both groups. Insulin resistance was defined by the index HOMA-IR. Eight patients had adequate weight, seven were overweight (4 preobese, 3 obese class I). Eight patients presented metabolic syndrome, five of whom with insulin resistance. The median levels of ghrelin, leptin and adiponectin of the patients did not differ from those of the controls. Ghrelin and adiponectin levels were correlated with each other; inversely correlated with BMI, waist circumference and triglyceride levels; and directly correlated with HDL-cholesterol. Leptin levels were inversely correlated with LDL-cholesterol and directly correlated with BMI, waist circumference, enzyme dosage, triglycerides, insulin, and HOMA-IR. Metabolic syndrome and overweight appear to be common in patients with GD type I on ERT. As leptin was strongly associated with insulin and HOMA index, it could become a biomarker to assess early evidence of insulin resistance in patients with GD. Further studies are needed to investigate the associations found.